QUANTITATIVE CALCULATION OF THE QUALITY OF TEACHING AS A PROJECT MANAGEMENT FACTOR OF THE INTERNATIONAL CONTRACT - Ryzhkov, Alexander S. (International Journal of Research -GRANTHAALAYAH, 2017)
One of the most problematic places in the implementation of international contracts is inefficient project management. The choice of inappropriate methodology for managing the educational project, irrational allocation of resources, untimely monitoring quality of the provided services can lead not only to the loss of an existing contract, but also to the reduction of the university's reputation in the international arena in conditions of competitive struggle in the educational services market. In turn, this minimizes the probability of concluding of new contracts. An innovative methodology for managing projects for the provision of educational services to a foreign customer has been developed. A general calculation of the quantitative assessment of a quality of the provision of an educational service is applied in this methodology. In order to significantly reduce the calculation time was created a universal computational program that allows processing of large data blocks with visualization of results in a two-dimensional coordinate system. The methodology was implemented in the NUOS workflow. The obtained results make possible to control the quality of rendering educational services to a foreign customer with minimum expenses of human resources and make adjustments to the educational process quickly if it necessary.